Deficiency of Adenosine Deaminase Type 2 (ADA2) DADA2 Masquerade as Lupus - Almabadi, Bayan; Alsuwat, Hesham; H Alsulami, Hasheema; Alkhammash, Salma (International Journal of Vasculitis, 2023)
DADA2 (deficiency of adenosine deaminase type 2) is an autoinflammatory autosomal recessive disease resulting from biallelic loss of function mutations in ADA2 gene. Clinical presentation and age of onset vary widely even among related patients, and variability of symptoms and severity manifestations include bone marrow failure, autoinflammation, immunodeficiency and vasculitis. Here, we report a case of young male with adult onset DADA2, who presented with fever, lower limbs skin rash, joint pain, and anemia resembling systemic lupus erythematous (SLE). DADA2 has an extremely variable clinical phenotype. It was described into three categories: inflammatory/vascular, immune dysregulation, and hematologic. However, the data is scant in describing autoimmunity phenotype in DADA2 and further studies are required to investigate the clinical correlation and presence of autoantibodies. We recommend genetic testing in cases with lupus-like disease especially if there is consanguinity between parents and family history of vasculitis.
Keywords: systemic lupus erythematous; vasculitis; adenosine deaminase type 2; immune deficiency